Risk Factors that Affect the Incidence of Ear Barotrauma in Traditional Diver Fishermen - Dulahu, Wirda Y.; Mursyidah, Andi; Pomalango, Zulkifli B. (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Barotrauma is a disease or trauma that occurs when a body experiences sudden changes in pressure when diving. One type of barotrauma that is often experienced by divers is ear barotrauma. The purpose of this study is to determine the risk factors (including age, disease history, depth of diving,dive duration, frequency of diving, rest duration, and diving procedures) that influence the incidence of barotrauma in traditional diver fishermen in BulawaSub-District, Bone Bolango Regency. The method conducted in this study is analytical quantitative method with cross sectional study approach. This studyis conducted through interview, observation, and measurement of divers’ hearing loss in divers. The samples in this study are 34 traditional diver fishermen in BulawaSub-District, Bone Bolango Regency. The results obtained p-value for age=0.039, working period=1,000, depth of diving =0.032, dive duration=1,000, frequency of diving =1,000, rest duration=1,000, and diving procedure=1,000. The conclusion of this study is that there is a relationship between the age and depth of diving toward the incidence of ear barotrauma in traditional diver fishermen, while the factors of working period, dive duration, frequency of diving, rest duration, and diving procedures are not related to the occurrence of ear barotrauma in traditional diver fishermen in Bulawa Sub-district Bone Bolango Regency.